Energy, greenhouse gas emissions and climate policies: Austria and Poland compared - Daniela Kletzan-Slamanig; Claudia Kettner (Austrian Institute of Economic Research (WIFO), 2023)
For the project "Social Aspects of Market-Based Instruments for Greenhouse Gas Emission Reductions - SoMBI" Austria and Poland were chosen as case study countries to compare the impacts of an EU-wide carbon price combined with different revenue recycling policies. The detailed analysis will focus on the macroeconomic and greenhouse gas emission effects of the introduction of the carbon pricing and revenue recycling schemes as well as the distributional effects of such price mechanisms for different household types. The two countries were chosen as they differ considerably in terms of their energy systems and economic conditions. Further differences regard the level of ambition of the respective domestic climate policies as well as the priorities set in energy policies. The aim of this paper is to provide indications of the sectors that are emission-intensive and/or labour-intensive and are likely to gain or lose from the chosen revenue recycling mechanisms. Moreover, the findings will provide background information for the interpretation of modelling results for the various carbon pricing and recycling options.
Keywords: 330; Treibhausgas-Emissionen; Ökosteuer; EU-Umweltpolitik; Kreislaufwirtschaft; Wirkungsanalyse; Vergleich; Polen; Österreich